Polymorphs of the Gadolinite‐Type Borates ZrB(2)O(5) and HfB(2)O(5) Under Extreme Pressure - Pakhomova, Anna (Chemistry, 2021)
Based on the results from previous high‐pressure experiments on the gadolinite‐type mineral datolite, CaBSiO(4)(OH), the behavior of the isostructural borates β‐HfB(2)O(5) and β‐ZrB(2)O(5) have been studied by synchrotron‐based in situ high‐pressure single‐crystal X‐ray diffraction experiments. On compression to 120 GPa, both borate layer‐structures are preserved. Additionally, at ≈114 GPa, the formation of a second phase can be observed in both compounds. The new high‐pressure modification γ‐ZrB(2)O(5) features a rearrangement of the corner‐sharing BO(4) tetrahedra, while still maintaining the four‐ and eight‐membered rings. The new phase γ‐HfB(2)O(5) contains ten‐membered rings including the rare structural motif of edge‐sharing BO(4) tetrahedra with exceptionally short B−O and B⋅⋅⋅B distances. For both structures, unusually high coordination numbers are found for the transition metal cations, with ninefold coordinated Hf(4+), and tenfold coordinated Zr(4+), respectively. These findings remarkably show the potential of cold compression as a low‐energy pathway to discover metastable structures that exhibit new coordinations and structural motifs.